Kromatografi Lapis Tipis (KLT): Pendekatan Pola Kromatogram Untuk Mengkonfirmasi Rhodamin B Pada Perona Pipi - Sania Puspita Sari; Retno Ikayanti; Elok Widayanti (State University of Gorontalo, 2022)
Blusher is a decorative cosmetic whose purpose is to beautify the face and emphasize the shape of the cheekbones. Rhodamine B is a synthetic dye in the form of a crystalline powder which is prohibited from being used in cosmetics according to the regulation by Head of The Indonesian Food and Drug Administration No. 18 of 2015 concerning Technical Requirements for Cosmetic Materials, because they are dangerous if contact with the skin. The purpose of this study was to determine rhodamine B in blusher which is traded in Kandat Market, Kediri Regency. In this study, five samples were used, namely sample A, sample B, sample C, sample D, and sample E. The qualitative analysis method used was Thin Layer Chromatography (TLC). In this method, the eluent N-butanol:ethyl acetate:ammonia is used in the ratio (55: 20: 25). TLC results showed visually in pink color, then when viewed under UV light 254 nm was yellow fluorescence. From the five samples, the Rf value was 0.52; 0.56; 0.61; 0.52 and 0.57, while the average Rf of the standard solution of rhodamine was 2.1. So that from the five samples it can be seen that they do not contain rhodamine B dye.